Biologically Active Preparation and Reproductive Function of Stud Rams - Shoinbayeva, Karligash Bolatovna (Asian Journal of Pharmaceutics (AJP), 2017)
Aims: This research work is aimed at studying the physico-chemical properties of the apistimul preparation created on the basis of drone homogenate and sodium chloride lyophilized by vacuum freeze-drying and studying the influence of this preparation on the productivity and the reproductive function of stud rams. Methods: The study uses the above-mentioned methods for determining physico-chemical properties of the preparation, quantitative and qualitative analysis for hormones, studying the quantity and quality of sperm of stud rams, some hematological characteristics of blood, fertility of ewes, and the offspring yield. Results: As a result of the studies, the physico-chemical composition of the preparation was determined, and the presence of biologically active substances and hormones – estradiol, testosterone, progesterone, cortisol, and prolactin – was established. Feeding the drug to animals increased the amount of hemoglobin and erythrocytes in the blood of experimental animals, improved the qualitative and quantitative characteristics of the ejaculate, and had a stimulating effect on the reproductive function of rams. Conclusion: When the apistimul preparation had been used as the source of medicinal and medical products, high-quality ejaculates were obtained that were inherent to healthy stud rams, and the expected effects of increasing resistance and reproductive function in animals were obtained.